In-vitro Selection of Drought Stress Tolerance in Rice (Oryza sativa L.) variety Tulasi and Sampada - Reddy, S. K.; Obaid, Omar H. (Indian Forester, 2021)
In the present investigation, the tissue culture technique was used to develop drought tolerant varieties Tulasi and Sampada to a higher level of tolerance by two stage. First exposing the callus produced from the mature embryo to different concentrations of PEG (0.0, 1, 2 and 3) % and second selecting the best tolerant cells of the drought and obtaining plants from them. The plants tested with same concentrations of PEG, in normal conditions (pots) and evaluated by some indicators proline, carbohydrate, K, Na and Cl.